Trends in the risk of mortality due to cardiovascular diseases in five Brazilian geographic regions from 1979 to 1996 - Souza,Maria de Fátima Marinho de (2001)
OBJECTIVE - To analyze the trends in risk of death due to cardiovascular diseases in the northern, northeastern, southern, southeastern, and central western Brazilian geographic regions from 1979 to 1996. METHODS - Data on mortality due to cardiovascular, cardiac ischemic, and cerebrovascular diseases in 5 Brazilian geographic regions were obtained from the Ministry of Health. Population estimates for the time period from 1978 to 1996 in the 5 Brazilian geographic regions were calculated by interpolation with the Lagrange method, based on the census data from 1970, 1980, 1991, and the population count of 1996, for each age bracket and sex. Trends were analyzed with the multiple linear regression model. RESULTS - Cardiovascular diseases showed a declining trend in the southern, southeastern, and northern Brazilian geographic regions in all age brackets and for both sexes. In the northeastern and central western regions, an increasing trend in the risk of death due to cardiovascular diseases occurred, except for the age bracket from 30 to 39 years, which showed a slight reduction. This resulted from the trends of cardiac ischemic and cerebrovascular diseases. The analysis of the trend in the northeastern and northern regions was impaired by the great proportion of poorly defined causes of death. CONCLUSION - The risk of death due to cardiovascular, cerebrovascular, and cardiac ischemic diseases decreased in the southern and southeastern regions, which are the most developed regions in the country, and increased in the least developed regions, mainly in the central western region.